Automated, Accelerated Nanoscale Synthesis of Iminopyrrolidines. Issue 30 (2nd March 2020) - Osipyan, Angelina; Shaabani, Shabnam; Warmerdam, Robert; Shishkina, Svitlana V.; Boltz, Harry; Dömling, Alexander
Abstract: Miniaturization and acceleration of synthetic chemistry is an emerging area in pharmaceutical, agrochemical, and materials research and development. Herein, we describe the synthesis of iminopyrrolidine‐2‐carboxylic acid derivatives using chiral glutamine, oxo components, and isocyanide building blocks in an unprecedented Ugi‐3‐component reaction. We used I‐DOT, a positive‐pressure‐based low‐volume and non‐contact dispensing technology to prepare more than 1000 different derivatives in a fully automated fashion. In general, the reaction is stereoselective, proceeds in good yields, and tolerates a wide variety of functional groups. We exemplify a pipeline of fast and efficient nanomole‐scale scouting to millimole‐scale synthesis for the discovery of a useful novel reaction with great scope. Abstract : The synthesis of iminopyrrolidine‐2‐carboxylic acid derivatives using chiral glutamine, oxo components, and isocyanide building blocks in an unprecedented Ugi 3‐component reaction is described. I‐DOT was used to prepare more than 1000 different derivatives in a fully automated fashion. The reaction is stereoselective, proceeds in good yields, and tolerates a wide variety of functional groups.